Interview with Old Town High School Student Emma Hargreaves - Lindsey, Ed (Maine Policy Review, 2017)
Old Town High School student Emma Hargreaves describes what she learned from working on a citizen science project a marine worm that is a pest of oysters.
Keywords: citizen science; high school; Maine